2019
DOI: 10.1186/s12889-019-7830-x
|View full text |Cite
|
Sign up to set email alerts
|

A research tool for measuring non-participation of older people in research on digital health

Abstract: BackgroundHealthcare services are being increasingly digitalised in European countries. However, in studies evaluating digital health technology, some people are less likely to participate than others, e.g. those who are older, those with a lower level of education and those with poorer digital skills. Such non-participation in research – deriving from the processes of non-recruitment of targeted individuals and self-selection – can be a driver of old-age exclusion from new digital health technologies. We aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 54 publications
0
45
1
7
Order By: Relevance
“…Moreover, in order to acknowledge future users’ interests and needs, the design and evaluation of interventions should involve samples of older people that reflect the target population of interest. 12 For example, this can mean involving older people from different age groups, with different attitudes to ICTs and with different cognitive and physical abilities.…”
Section: Take-home Messagesmentioning
confidence: 99%
“…Moreover, in order to acknowledge future users’ interests and needs, the design and evaluation of interventions should involve samples of older people that reflect the target population of interest. 12 For example, this can mean involving older people from different age groups, with different attitudes to ICTs and with different cognitive and physical abilities.…”
Section: Take-home Messagesmentioning
confidence: 99%
“…The current study was aimed to see the effects lockdown of COVID-19 on the sexual life of the individuals from three south-east Asian countries. The participants of this study have either graduate or postgraduate education and employed, which is expected as most of online or web survey respondents are younger with high education and most likely employed than those who refuse to participate in the survey (Cantuaria and Blanes-Vidal, 2019;Poli et al, 2019).…”
mentioning
confidence: 99%
“…We observed that many patients who would normally not be considered ideal candidates for the program were readily onboarded despite concerns regarding their technological or health literacy levels. Patients of varying backgrounds used the program beyond expected levels of success; this finding helped challenge the paradigm regarding the characteristics of an “ideal” program candidate [ 18 ]. Often, with these biases, many virtual care interventions fail to serve patient groups that are most in need of support [ 19 ].…”
Section: Discussionmentioning
confidence: 99%